2017
DOI: 10.3847/1538-3881/153/2/67
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF A HYDROGEN CORONA IN HST Lyα IMAGES OF EUROPA IN TRANSIT OF JUPITER

Abstract: We report far-ultraviolet observations of Europa in transit of Jupiter obtained with the Space Telescope Imaging Spectrograph of the Hubble Space Telescope on six occasions between 2014 December and 2015 March. Absorption of Jupiter's bright hydrogen Lyα dayglow is detected in a region several moon radii above the limb in all observations. The observed extended absorption provides the first detection of an atomic hydrogen corona around Europa. Molecular constituents in Europa's global sputtered atmosphere are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 48 publications
5
39
2
Order By: Relevance
“…The vertical column densities derived for Callisto's H corona are similar (visit 1) or ∼ 3× higher (visit 2) compared to the vertical column density found for Europa of (2.3-3.5) ×10 11 cm −2 [Roth et al, 2017] [Smyth and Marconi, 2006;Marconi, 2007], and directly from ion sputtering and radiolysis in the icy surface . Loss of H from the atmosphere is dominated by thermal escape and by reactions with the surface, leading to a dip in density at low altitudes (<50 km) in the modeled abundance profiles [Liang et al, 2005;Marconi, 2007].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The vertical column densities derived for Callisto's H corona are similar (visit 1) or ∼ 3× higher (visit 2) compared to the vertical column density found for Europa of (2.3-3.5) ×10 11 cm −2 [Roth et al, 2017] [Smyth and Marconi, 2006;Marconi, 2007], and directly from ion sputtering and radiolysis in the icy surface . Loss of H from the atmosphere is dominated by thermal escape and by reactions with the surface, leading to a dip in density at low altitudes (<50 km) in the modeled abundance profiles [Liang et al, 2005;Marconi, 2007].…”
Section: Discussionsupporting
confidence: 57%
“…The vertical column densities derived for Callisto's H corona are similar (visit 1) or ∼3× higher (visit 2) compared to the vertical column density found for Europa of (2.3–3.5) ×10 11 cm −2 [ Roth et al , ]. The vertical column density derived for Ganymede's H corona of ∼2.4 × 10 12 cm −3 [ McGrath et al , ] is somewhat higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na and K were measured (Brown, 2001) in the extended exosphere of Europa, at distances of 6 -13 R E , with transverse column densities of N C (Na) = (1.5 -3.7) · 10 9 cm -2 and N C (K) = (4.5 -13) · 10 7 cm -2 , and a Na/K ratio in Europa's extended atmosphere of 25±2. Recently, Roth et al (2017) reported HST observations of the H corona at Europa from which they derived maximum exospheric densities at the surface in the range of (1.5-2.2)·10 3 cm −3 , confirming the abundances predicted by Monte Carlo simulations (Smith and Marconi 2006;Wurz et al, 2014). A recent review of the chemical 6 composition and densities profiles for the relevant release processes was given by Vorburger and Wurz (2017).…”
Section: Europa's Exospheresupporting
confidence: 57%
“…In their December 2012 dataset, Roth et al (2014) detected localized off-limb hydrogen and oxygen emissions near Europa's south pole, which they used to infer an active water plume. A lack of similar detections in the other 19 visits indicates that such events are rarely detectable in this type of observation, though subsequent work by other groups using a variety of methods support the presence of sporadic plume activity originating from a few distinct surface locations (Sparks et al 2016;McGrath and Sparks 2017;Jia et al 2018 (Roth et al 2017). In addition, both Na and K have been observed in Europa's extended atmosphere (> 5R Europa ); the relative abundance of these species is different from that of Io and of micrometeorites, suggesting an endogenic origin of this alkali material (Brown and Hill 1996;Brown 2001).…”
Section: Introductionmentioning
confidence: 87%